Eco-friendly innovations in electricity transmission and distribution networks - Bessede, Jean-Luc (Woodhead Publishing in energy ;, 2015)
Electricity transmission and distribution (T & D) networks carry electricity from generation sites to demand sites. With the increasing penetration of decentralised and renewable energy systems, in particular variable power sources such as wind turbines, and the rise in demand-side technologies, the importance of innovative products has never been greater. Eco-design approaches and standards in this field are aimed at improving the performance as well as the overall sustainability of T & D network equipment. This multidisciplinary reference provides coverage of developments and lessons-learned in.